1996
DOI: 10.1046/j.1471-4159.1996.67031324.x
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin (Apo J) Protects Against In Vitro Amyloid‐β(1–40) Neurotoxicity

Abstract: Clusterin is a secreted glycoprotein that is markedly induced in many disease states and after tissue injury. In the CNS, clusterin expression is elevated in neuropathological conditions such as Alzheimer's disease (AD), where it is found associated with amyloid-/3 (A/I) plaques. Clusterin also coprecipitates with A/I from CSF, suggesting a physiological interaction with A/I. Given this interaction with A/I, the goal of this study was to determine whether clusterin could modulate A/I neurotoxicity. A mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 24 publications
3
52
0
Order By: Relevance
“…[111][112][113][114] ApoJ has been shown to interact with Ab 115-117 and alter its ability to form fibrils [117][118][119] and modifies Abmediated neurotoxicity. 32,119,120 It has also been shown in vivo that expression of apoJ either on its own or together with apoE reduces plaque formation, soluble and insoluble brain Ab40/42 levels and CSF Ab40/42 levels in PDAPP transgenic mice. 121 This effect was shown not to be because of altered Ab production, as APP processing was not altered in the presence or absence of apoE and/or apoJ.…”
Section: Apolipoprotein J-mediated Transport Of Ab Across Bbbmentioning
confidence: 99%
“…[111][112][113][114] ApoJ has been shown to interact with Ab 115-117 and alter its ability to form fibrils [117][118][119] and modifies Abmediated neurotoxicity. 32,119,120 It has also been shown in vivo that expression of apoJ either on its own or together with apoE reduces plaque formation, soluble and insoluble brain Ab40/42 levels and CSF Ab40/42 levels in PDAPP transgenic mice. 121 This effect was shown not to be because of altered Ab production, as APP processing was not altered in the presence or absence of apoE and/or apoJ.…”
Section: Apolipoprotein J-mediated Transport Of Ab Across Bbbmentioning
confidence: 99%
“…In all our experiments, the oligomers are formed before adding the chaperones, showing that the protective action of the latter also includes neutralization of toxic oligomers after they have formed. This protective mechanism is not entirely undescribed, but evidence has been very sparse in the past, with reports often being contradictory and with undefined mechanisms (9,(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…When tested against neuronal cell lines, under certain specific conditions, clusterin and α 2 M were shown to promote the neurotoxicity of Aβ (clusterin -PC12 cells (Oda et al, 1995); α 2 M -LAN5 cells (Fabrizi et al, 2001)). In stark contrast, using primary rat mixed neuronal cultures, others have demonstrated that clusterin and α 2 M can protect cells from Aβ toxicity (Boggs et al, 1996;Du et al, 1997). Even within individual studies, depending on the conditions used, clusterin was shown both to protect cells and to promote cytotoxicity.…”
Section: The In Vitro Effects Of Ecs On Amyloid Toxicitymentioning
confidence: 95%